Research of mineral elements in Cosmos bipinnatus Cav. raw materials - Deineka, Amina; Zhuravvel, Iryna (Annals of Mechnikov’s Institute, 2023)
Introduction. Mineral elements accumulate in various parts of plants and enter the human body with food, dietary supplements and herbal medicinals. It is known that macro- and microelements are involved in many metabolic processes. Mineral elements in plant raw materials are contained in a bioavailable form for the body, as a result of which they actively affect the state of health, can show both medicinal properties and have a toxic effect. Therefore, the study of the mineral composition of plant raw materials is relevant. We have continued the study of Cosmos bipinnatus Cav. of the Asteraceae family, which was grown in Ukraine. Previously, the mineral elements of this species were not studied, so it was appropriate to study them for further standardization of raw materials and the development of herbal medicinals based on them. Research results. The total ash content in seeds (4.73 ± 0.15%), stems (5.86 ± 0.18%), grass (10.82 ± 0.32%), leaves (12.04 ± 0 ,36 %), flowers (8.79 ± 0.26 %) and roots (6.37 ± 0.19 %) of Cosmos bipinnatus Cav. According to the results of the experiment, 19 elements were identified and their content was determined in all samples of the raw material of Cosmos bipinnatus Cav. The total content of elements (mg/100 g) was the highest in leaves (5445.94 ± 163.38) and grass (5220.15 ± 156.61), slightly lower in flowers (4042.01 ± 121.26); in roots (3794.43 ± 113.83), stems (2711.20 ± 81.34) and seeds (2297.38 ± 68.92) mineral elements were determined in smaller quantities. Among the elements in all studied samples, potassium and calcium prevailed in terms of content. Molybdenum (0.05 ± 0.01 mg/100 g - 0.11 ± 0.01 mg/100 g) and nickel, the maximum content of which was observed in the roots of the plant (0.11 ± 0, 01 mg/100 g). The ratio of the interdependent tandem of potassium: sodium in seeds was almost 1:40, stems – 1:58, grass – 1:35, leaves – 1:33, flowers – 1:87, roots – 1:21. The highest calcium content was recorded in the leaves of Cosmos bipinnatus Cav. (1200.00 ± 36.00 mg/100 g). The content of iron (64.00 ± 1.92 mg/100 g), silicon (510.00 ± 15.30 mg/100 g), aluminum (76.80 ± 2.31 mg/100 g), zinc (10.90 ± 0.33 mg/100 g) and copper (3.20 ± 0.09 mg/100 g) was higher in the roots of the plant. In seeds (10.30 ± 0.31 mg/100 g) and roots (10.20 ± 0.31 mg/100 g), the strontium content was almost unchanged. The content of heavy metals was within the limits of the requirements put forward by the Federal State Food and Drug Administration for plant raw materials. Conclusions. The conducted studies of the mineral composition of the seeds, stems, grass, leaves, flowers and roots of Cosmos bipinnatus Cav. deepen the information about its chemical composition, which can be useful for the further development of medicinal products based on it and prove that the content of heavy metals in the studied samples of raw materials was within the requirements of the State Federal Office for Medicinal Plant Materials. The results of determining the content of total ash and the mineral composition of the researched raw material of Cosmos bipinnatus Cav. will be used for its standardization and the development of herbal medicinal products. Keywords: Cosmos bipinnatus (Cav.), mineral elements, atomic emission spectrometry, identification, quantitative content.